Clusters as a Tool for Raising Tourism Competitiveness of a Region (on the Example of the Land of Loess Gorges in Lubelskie Voivodship) - Andrzej Miszczuk (Barometr Regionalny)
The aim of the article is to analyze a case study of a successfully developing tourism cluster, named the Land of Loess Gorges, located in the western part of Lubelskie Voivodship and consisting of 11 communes. The content of the present study consists of: (1) a synthetic description and typology of clusters, taking into account the specificity of tourism clusters; (2) an assessment of tourism potential (in the natural and cultural dimension) of the Land of Loess Gorges; (3 ) an analysis and evaluation of tourism products offered by this cluster and their impact on tourism competitiveness of the Lubelskie Voivodship.